Penerapan Metode Taguchi-GRA untuk Optimasi Kebulatan, MRR dan Kekasaran Permukaan pada Proses Bubut - Am. Mufarrih; Hesti Istiqlaliyah (Badan Kerja Sama Teknik Mesin Indonesia, 2018)
This research was conducted to optimize turning process with several quality characteristics based on orthogonal array using Taguchi-GRA method. Experiments were carried out by varying the turning process variables such as depth of cut, material removal rate and cutting speed. Some of the quality characteristics that are optimized are roundness, MRR and surface roughness. The experimental design uses L9 orthogonal array. The experimental results show that machining performance in the turning process can be effectively improved through this method. The GRG value representing several quality characteristics increased by 34% from 0.7017 to 0.9403.